The culture of official statistics. Symbolic domination and “bourgeois” assimilation in quantitative measurements of immigrant integration in Germany - Martin Petzke (Theory and Society, 2022)
While cultural sociology has recently made a comeback in research on social inequality both in the context of poverty studies and studies of immigrant integration, it has rarely investigated how particular constructions of the problem of socioeconomic mobility are themselves culturally situated. The article addresses this neglect by investigating the problematization of disadvantaged lives within the relational framework of Bourdieu's cultural theory of the state. Here, the state exercises symbolic violence by transforming one arbitrary cultural standpoint in social space into a universal standard, or a taken-for-granted "doxa," against which other cultural positions can only come off as deficient. The article extends this perspective by addressing the role of official statistics in this process. Taking Germany's official monitoring of the socioeconomic integration of immigrants as its case and drawing from document analysis, interviews, ethnographic observation, and data from the German General Social Survey, the article shows how such statistical instruments of the welfare state in fact tacitly universalize a model of the good life particular to civil servants, the very constructors of the monitors, as a benchmark for immigrant integration.
Keywords: 300; Culture; Pierre Bourdieu; Quantification; Social Inequality; State; Symbolic domination; Language; Communication and Culture; Studies in Human Society